Concentrated protein solutions investigated using acoustic levitation and small‐angle X‐ray scattering. (12th February 2020) - Sønderby, Pernille; Söderberg, Christopher; Frankær, Christian G.; Peters, Günther; Bukrinski, Jens T.; Labrador, Ana; Plivelic, Tomás S.; Harris, Pernille
Abstract : An acoustically levitated droplet has been used to collect synchrotron small‐angle X‐ray scattering at very high protein concentrations (>200 mg ml −1 ) – difficult to measure in standard flow‐through cells. The data can be collected with minimal sample consumption. Details of the methodology and data treatment are shown thoroughly. Abstract : An acoustically levitated droplet has been used to collect synchrotron SAXS data on human serum albumin protein solutions up to a protein concentration of 400 mg ml −1 . A careful selection of experiments allows for fast data collection of a large amount of data, spanning a protein concentration/solvent concentration space with limited sample consumption (down to 3 µL per experiment) and few measurements. The data analysis shows data of high quality that are reproducible and comparable with data from standard flow‐through capillary‐based experiments. Furthermore, using this methodology, it is possible to achieve concentrations that would not be accessible by conventional cells. The protein concentration and ionic strength parameter space diagram may be covered easily and the amount of protein sample is significantly reduced (by a factor of 100 in this work). Used in routine measurements, the benefits in terms of protein cost and time spent are very significant.